PERAN PERSEPSI TENTANG PSYCHOSOCIAL HAZARD DAN KEPUASAN KERJA TERHADAP BURNOUT - , AGATHA SAGITA RIA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Burnout was a representative from syndrome of psychological stress, in which showed a negative response as a result from workâs pressure it self. The aim of this study to knew whether perception of psychosocial hazard and job satisfaction had contribution toward the uprising of burnout in work place. This study involved 148 employees in electrical section of PT. X. The analysis used multiple regression. The result showed contribution from employeeâs perception of psychosocial hazard and job satisfaction toward burnout in workplace with F = 9,139 and p significant at 0,000.